NEWSPAPERS AS DA'WAH MEDIA - supratman, Supratman supratman; Sakinah (JURNAL ILMU BUDAYA, 2023)
Da'wah media is one of the elements of da'wah that can support the success of da'wah. The message of da'wah in the verses of the Al-Quran emphasizes the call for goodness. One of the ways this form of kindness is that the material da'wah that will be delivered must be adapted to the media that will be used. The development of very diverse da'wah media in society (for example television, the internet, etc.), makes it easier for people to gain enlightenment in religion without having to meet face to face.